Self-assessment model for digital retrofitting of legacy manufacturing systems in the context of industry 4.0 - Alqoud, Abdulrahman; Milisavljevic-Syed, Jelena; Salonitis, Konstantinos (University of Novi Sad, 2025)
In the current competitive landscape, digital retrofitting of legacy manufacturing systems is crucial for maintaining a competitive edge. Digital retrofitting involves adapting existing systems to modern technologies to enhance efficiency and capabilities. To select the most appropriate retrofitting approach, an assessment model is required due to the diversity of legacy systems and the varying readiness levels of organizations. In this study, a comprehensive assessment model is designed for Small and Medium Manufacturing Enterprises (SMMEs) to facilitate digital retrofitting strategies. The model starts with a questionnaire to evaluate existing systems, followed by a classification of maturity levels, and then provides tailored recommendations, aiming to guide SMMEs in successfully integrating Industry 4.0 technologies. The methodology includes a literature review and surveys, which were used to develop, test, and refine the model. The model assesses 21 items across four dimensions, Strategy and Organization, Development of the Workforce, Smart Factory, and Smart Process, using a five-point scale. Furthermore, the model introduces a four-level maturity classification for digital transformation in manufacturing and offers customized recommendations. The validation through the surveys involves content validity testing with 18 industry practitioners and a pilot study with a sample of 32 SMMEs.